Description of Erythrocyte Sedimentation Rate (ESR) Levels Among Arthritis Patients Receiving NSAID Therapy at Betungan Public Health Center, Bengkulu City - Eprillia Masrianti; Putri Widelia (POLTEKKES KEMENKES BENGKULU, 2026)
Background :Arthritis is a chronic systemic inflammatory disease characterized by inflammation and swelling of the joints. One important laboratory parameter used to assess inflammatory activity is the Erythrocyte Sedimentation Rate (ESR). Arthritis patients commonly receive Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) to reduce pain and inflammation. Causing ESR levels to remain abnormal as the disease progresses. This study aimed to describe ESR levels among arthritis patients receiving NSAID therapy at Betungan Public Health Center, Bengkulu City, in 2025. Methods : This study used a descriptive observational design. Samples were collected using an accidental sampling technique involving 35 respondents. ESR examinations were performed automatically using the ESR Analyzer (MICROsed System) at the Laboratory of the Medical Laboratory Technology Department, Poltekkes Kemenkes Bengkulu. Data were analyzed descriptively and presented in the form of frequency distribution tables and percentages. Results : Among the 35 respondents, most were female (94.29%) with an average age of 46.7 years. The longest duration of NSAID consumption was long-term use (>12 weeks), accounting for 45.7% of respondents. ESR examination results showed that most respondents had abnormal ESR levels, totaling 26 people (74.29%), while respondents with normal ESR levels totaled 9 people (25.71%). Conclusion :In conclusion, while NSAID therapy successfully manages the clinical symptoms of arthritis patients at the Betungan Public Health Center, it is insufficient for normalizing systemic inflammatory markers, as evidenced by the high prevalence of abnormal ESR levels (74.29%). This lack of laboratory normalization is particularly pronounced among female and elderly patients due to their physiological predisposition to elevated ESR.